2013
DOI: 10.1002/dvdy.24065
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial‐derived adrenomedullin drives cardiac hyperplasia during embryogenesis

Abstract: Background Growth promoting signals from the epicardium are essential for driving myocardial proliferation during embryogenesis. In adults, these signals become reactivated following injury and promote angiogenesis and myocardial repair. Therefore, identification of such paracrine factors could lead to novel therapeutic strategies. The multi-functional peptide adrenomedullin (Adm = gene, AM = protein) is required for normal heart development. Moreover, elevated plasma AM following myocardial infarction offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 83 publications
(119 reference statements)
4
33
0
Order By: Relevance
“…AM binds RDC1/CXCR7 with a K d of 1.9 ×10 −7 M, similar to CLR when associated with RAMPs (Kapas and Clark, 1995). Importantly, we have recently shown that genetic overexpression of AM ligand in Adm hi/hi mice results in gross cardiac enlargement due to cardiac hyperplasia during embryogenesis (Wetzel-Strong et al, 2013), which closely phenocopies the dysmorphic cardiac hyperplasia of Cxcr7 −/− mice.…”
Section: Introductionmentioning
confidence: 96%
“…AM binds RDC1/CXCR7 with a K d of 1.9 ×10 −7 M, similar to CLR when associated with RAMPs (Kapas and Clark, 1995). Importantly, we have recently shown that genetic overexpression of AM ligand in Adm hi/hi mice results in gross cardiac enlargement due to cardiac hyperplasia during embryogenesis (Wetzel-Strong et al, 2013), which closely phenocopies the dysmorphic cardiac hyperplasia of Cxcr7 −/− mice.…”
Section: Introductionmentioning
confidence: 96%
“…26 AM RECRUITMENT OF UNK CELLS IS DOSAGE-DEPENDENT Subsequent studies of a gene-targeted murine model of Adm overexpression (Adm hi allele, which expresses Adm at levels three-fold higher than the wild-type allele) determined that uNK cell recruitment to the decidua by AM is dosage-dependent. 5,28 Specifically, Adm hi/hi placentas demonstrated a 30% increase in uNK cells. 28 Because the uNK cells in these placentas were labeled with Dolichos biflorus agglutinin lectin, we can conclude that the uNK cell population that was quantified is, in fact, the one that expands during pregnancy.…”
Section: Maternal-derived Am Is Necessary For Successful Implantationmentioning
confidence: 96%
“…4,5 AM belongs to the calcitonin/calcitonin gene-related peptide family, which binds various combinations of G-coupled protein receptors and their associated receptor activity modifying proteins. The canonical receptor for AM is calcitonin receptor-like receptor when associated with either receptor activity modifying protein 2 or 3.…”
Section: Am Is a Versatile Peptide Hormone Expressed By Both Maternalmentioning
confidence: 99%
“…This difficulty was particularly apparent in Cxcr7-null mice, which exhibited cardiac enlargement and hyperplasia, a phenotype that was not observed in mutant mice of the canonical ligands, SDF-1 and CXCL11 [21,61,62]. However, the cardiac phenotypes closely phenocopied a genetic model of AM overexpression (known as Adm hi/hi mice) which results in gross cardiac hyperplasia during embryogenesis [25,63]. The similarity in cardiac phenotypes and the historical association of AM and CXCR7 sparked curiosity about whether CXCR7 could behave as a decoy receptor for AM.…”
Section: Adrenomedullin During Lymphatic Vascular Developmentmentioning
confidence: 99%
“…It will be interesting to tease out whether levels of AM originating outside of the tumor impact cancer progression via lymphangiogenesis. Adm overexpression models may prove useful in determining host AM status on tumor progression [63].…”
Section: Adrenomedullin-induced Lymphangiogenesis In the Reproductivementioning
confidence: 99%